Active pulmonary interstitial fibrosis in a COVID-19 survivor diagnosed by transbronchial lung cryobiopsy six months after onset - Yutaka Muto; Koji Okudela; Atsuhito Nakazawa; Kakeru Hisakane; Mai Matsumura; Tamiko Takemura; Tae Iwasawa; Takashi Ogura (Elsevier, 2022)
We present a 76-year-old man who visited our center because of persistent dyspnea with hypoxia on exertion 6 months after onset of coronavirus disease 2019. Chest computed tomography showed bilateral extensive subpleural reticulation with traction bronchiectasis predominantly in the lower lung lobes. Transbronchial lung cryobiopsy revealed spatially and temporally intermittent interstitial fibrosis with mild lymphoid cell infiltration. Not only were there membranous fibrotic scars on the alveolar septa, but there were scattered foci of alveolar collapse with young fibroblastic proliferations, suggesting progressive interstitial fibrotic lesions. In addition to fibrotic phase of diffuse alveolar damage, the acceleration of subclinical preexisting interstitial lung abnormalities might have affected his respiratory condition.